On the 'New Anti-Semitism' and Its Political and Religious Consequences. Issue 2 (November 2018) - Davidson, Lawrence
Abstract : The so-called 'new anti-Semitism' is an artificial construct created by Israel to counter growing popular opposition to its own racist policies. Loss of popular support means Israeli influence has been largely restricted to governing circles vulnerable to Zionist lobby pressure. The appearance of the new anti-Semitism has also created a tragic paradox particularly for Jews who believe in tolerance, diversity and human rights. For, if one accepts the precepts of the new anti-Semitism, to stand against Israeli racist policies and practices, you yourself must be deemed racist. In turn, the paradox has created an existential crisis of conscience for Jews worldwide.